Model Hibrid Keamanan Komunikasi Data Menggunakan Kriptografi Berbasis Federated Lattice Dan Stegnografi Homomorfik Dengan Optimasi Quantum-Resistant Protocol - Yekti Kuncorojati; Metha Mudrifah Zain; Sindy Hertika Putri Sindy; Kartika Imam Santoso; Andri Triyono (Julia: Jurnal Ilmu Komputer An Nuur, 2026)
Data communication security faces significant challenges with the development of quantum computing and the increasing complexity of cyberattacks. This research proposes an innovative hybrid model that combines Federated Lattice-based Cryptography (FLC) and Homomorphic Steganography (HS) with optimization of Quantum-Resistant Protocol (QRP) for data communication security. This hybrid approach addresses the weaknesses of conventional methods by providing layered security that is resistant to quantum threats and advanced persistent threat attacks. The research methodology uses an experimental approach with the simulation of attacks in a controlled communication environment. Results show that the proposed hybrid model increases resilience against side-channel attacks by 97.3%, reduces latency overhead by up to 42% compared to conventional post-quantum methods, and guarantees mathematical security even in the presence of an adversary with limited quantum computing capabilities. The main contribution of this research is the development of the FLC-HS-QRP algorithm that combines lattice-based key federation with homomorphic steganography in a quantum-resistant communication protocol, as well as parameter optimization for implementation on resource-limited devices. This research fills a critical gap in the literature on communication security and offers a practical approach to securing data communication in the era of quantum computing.